2013
DOI: 10.1182/blood-2012-10-460618
|View full text |Cite
|
Sign up to set email alerts
|

Runx3 deficiency results in myeloproliferative disorder in aged mice

Abstract: Key Points Runx3 conditional knockout mice develop a myeloproliferative disorder when aged. Runx3-deficient cells show hypersensitivity to G-CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…[21][22][23][24] Here we show that Runx1 deletion led to Runx3 upregulation in HSCs. Our data together with data from a recent study demonstrating a functional role of Runx3 in HSCs 25 suggests that Runx3 partially substitutes for Runx1 function. The functional redundancy of Runx factors was further supported by a report showing Runx2 upregulation in MLL-AF9 leukemia.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[21][22][23][24] Here we show that Runx1 deletion led to Runx3 upregulation in HSCs. Our data together with data from a recent study demonstrating a functional role of Runx3 in HSCs 25 suggests that Runx3 partially substitutes for Runx1 function. The functional redundancy of Runx factors was further supported by a report showing Runx2 upregulation in MLL-AF9 leukemia.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, it was shown recently that Runx3 has an antiproliferative function in HSCs and/or progenitors of aged mice. 25 In this report, using a knockin mouse model in which binding of all Runx factors at the 214kb upstream enhancer of PU.1 is abolished, 11 we could rule out any compensatory effects of individual Runx family members. By using this model, we observed major importance of the Runx-PU.1 pathway for HSC function.…”
Section: Introductionmentioning
confidence: 83%
“…We saw a Pb-dependent increase in DNA methylation for another member of Runt domain associated transcription factor, RUNX3 (Table 2 & Supplementary Figure 1B) only in females. RUNX3 deficiency is shown to be associated with myeloproliferative disorder in mouse [59]. Wolff et al reported that the DNA methylation of RUNX3 increases with age and the process is further accelerated by smoking [60].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of Runx1 or Cbfb function caused by chromosomal translocations is frequently found in human acute myelogenous leukemia (AML), 10 whereas Runx3 deficiency has been implicated in myeloproliferative diseases (MPDs) in aged mice. 11 Although Runx1 is essential for HSC formation from hemogenic endothelial cells during embryogenesis, conditional deletion of Runx1 in HSCs neither influences the survival of mice nor the maintenance of long-term HSCs. 12,13 By contrast, Runx1 is required for the development of B and T lymphocytes and megakaryocytes, [14][15][16][17] suggesting that it functions in cell fate decisions during BM progenitor differentiation.…”
Section: Introductionmentioning
confidence: 99%